2022
DOI: 10.3390/toxics10110665
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Consumption of Food-Derived Chlorogenic Acid Protects Mice against Acetaminophen-Induced Hepatotoxicity via Promoting PINK1-Dependent Mitophagy and Inhibiting Apoptosis

Abstract: Hepatotoxicity brought on by acetaminophen (APAP) is significantly impacted by mitochondrial dysfunction. Mitophagy, particularly PINK1-mediated mitophagy, maintains the stability of cell function by eliminating damaged mitochondria. One of the most prevalent dietary polyphenols, chlorogenic acid (CGA), has been shown to have hepatoprotective properties. It is yet unknown, nevertheless, whether its defense against hepatocyte apoptosis involves triggering PINK1-mediated mitophagy. In vitro and in vivo models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“… 6 , 39 Increased apoptosis may thus reduce hepatic injury by triggering a switch to necroptosis through the activation of the TNF signaling pathway during AILI. Consistent with previous studies, 40 , 41 we found that apoptosis was increased in AILI animal and hepatic models. In vitro , we demonstrated that the apoptosis and TNF-α levels were regulated by BTF3L4 in normal liver cells without any treatment.…”
Section: Discussionsupporting
confidence: 93%
“… 6 , 39 Increased apoptosis may thus reduce hepatic injury by triggering a switch to necroptosis through the activation of the TNF signaling pathway during AILI. Consistent with previous studies, 40 , 41 we found that apoptosis was increased in AILI animal and hepatic models. In vitro , we demonstrated that the apoptosis and TNF-α levels were regulated by BTF3L4 in normal liver cells without any treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that the hepatotoxicity of APAP can lead to mitochondrial dysfunction and affect PINK1-mediated mitosis. Chlorogenic acid stabilizes cell function by eliminating mitochondrial damage, increases PINK1-dependent mitosis, inhibits apoptosis of liver cells, and prevents APAP hepatotoxicity ( Hu et al, 2022 ). Currently, chlorogenic acid is considered a promising hepatic detoxifier for APAP.…”
Section: Effects and Mechanism Of Natural Products In Acetaminophen-i...mentioning
confidence: 99%
“…CGA mitigates acetaminophen-induced hepatic injuries by inhibiting apoptosis and oxidation, ameliorating liver inflammation, activating Nrf2, promoting mitophagy, and suppressing activities of metabolic enzymes such as cytochrome P450 (CYP) [20,24,[150][151][152][153][154]. CGA can ameliorate hepatotoxicity triggered by many other drugs including tamoxifen, methotrexate, triptolide, and monocrotaline [155][156][157][158].…”
Section: Hepatoprotectionmentioning
confidence: 99%
“…Anti-inflammatory and oxidative effects (Sections 2.1 and 2.3) Macrophage [32]; 3T3-L1 cells [27]; carbon tetrachloride or acetaminophen-induced liver injury in mice [20,23,24] Weaned Pigs, LPS-induced mice, I/R rat liver injury, endotoxic shock-induced acute liver injury [28,30,31,33] Suppressing TLR4, TNF-α, NF-κB, and MAPK pathways [28][29][30][31]; activation of CD36/AMPK/PGC-1α [32] and Nrf2 signaling [20,34- Metals, chemicals, and toxins: sodium arsenite [137], Pb [138], Cd [139], aluminum chloride [140], polychlorinated biphenyls [141], TAA [142], CCl4 [143], D-gal [144], L-carnitine [145], LPS [146,147], palmitic acid [148], and aflatoxin B1 [149] Activating the Nrf2 pathway, promoting mitophagy, and suppressing the TLR4/NF-κB pathway [20,24,[150][151][152][153][154][155][156][157][158][159] CGA Neuronal cells and PC12 cells [34,191]; oligodendrocyte [196] and OL cell line M03-13…”
Section: Inflammation and Oxidationmentioning
confidence: 99%